PENERAPAN METODE FAHIM QURAN (TINGKAT DASAR) PADA PENGAJIAN QUR’AN ANAK DAN REMAJA DI RANTING MUHAMMADIYAH MENUJU PEMBERDAYAAN CABANG DAN RANTING DI KOTA MEDAN - Dedi Amrizal (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2017)
This community service was conducted to re-establish the activity of reciting Al-Quran by the children and adolescents before ‘Isha which was commonly done in the masjid of Muhammadiyah. The target of activity was the students and the members of Youth Muhammadiyah or NA who were active in organizations and in masjid and they were from Muhammadiyah family. They were trained to be teachers of reciting al-Quran to the children by using the method of Fahim Quran. These teachers were trained for a month about using the basic Fahim Quran method that contained Makhaarijul Huroof, sifaatul huroof, tajweed, and good memorization of short surahs of Juz ‘Amm. The next step was to improve their ability to interpret and understand the Qur'an properly and correctly by using the method of Fahim quran. The specific target of this activity was to empower the young generation in Muhammadiyah organization and to open recruitment opportunities from the children of the community around Masjid of Muhammadiyah who participated in this program.